Potentiometric Monitoring of Co2+ Ion at Nano Scale Based on Hydrazinecarbothioamide Derivatives by Fabrication of Coated Pyrolytic Graphite Electrode. Issue 7 (3rd May 2016) - Sahani, Manoj Kumar; Gupta, Neha; Singh, A. K.; Jain, A. K.
Abstract : Hydrazinecarbothioamide derivative based ligands 2, 2 ′ -(((ethane-1, 2-diylbis-(oxy))bis(3-methoxy-4, 1-phenylene))bis-(methanylylidene))bis(hydrazinecarbothioamide) (L1 ), 2, 2 ′ -(((propane-1, 3-diylbis(oxy))bis(3-methoxy-4, 1-phenylene))bis-(methanylylidene))bis-(hydraznecarbothioamide) (L2 ) and 2, 2 ′ -((((oxybis(ethane-2, 1-diyl))bis(oxy))bis(3-methoxy-4, 1-phenylene))bis(methanylylidene))bis(hydrazinecarbothioamide) (L3 ) were synthesized and investigated as monitoring probe for Co 2+ ion. Fabricated coated graphite electrode (CGE) and coated pyrolytic graphite electrode (CPGE) were prepared and CPGE explored the best performance with optimized membrane composition L2 : PVC: 1-CN: KTpClPB ≡ 6:35:56:3 (w/w, mg). CPGE showed low detection limit of 6.1 × 10 −9 mol L −1, Nernstian compliance (29.4 ± 0.6 mV decade −1 of activity), wide working pH range (3.0–8.5) and fast response time (7 s). The sensor is practically applicable in real samples and used as an indicator electrode in the potentiometric titration of Co 2+ ion with EDTA.